Deciphering invasive breast cancer heterogeneity for personalised therapy - Althobiti, Maryam (2021)
Background and Aims: Characterisation of molecular and cellular heterogeneity in breast cancer (BC) is crucial to refine the prognostic classification of BC and understand the development of treatment resistance. This study investigated the hypotheses that: (i) molecular heterogeneity in terms of expression of BC stem cell (BCSC) markers, oestrogen receptor alpha (ER) and ER-related biomarkers, and the density of tumour-infiltrating lymphocytes (TILs) exists within individual tumours and also between different tumours, and (ii) assessment of such heterogeneity using high-throughput pathological techniques may help to predict tumour progression and patient outcomes.